Response of Sweet Corn (Zea mays L. Saccharata) Growth on the Treatment of Organic and NPK Fertilizer - Ahmad Raksun; I Wayan Merta; I Gde Mertha; Mohammad Liwa Ilhamdi (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2021)
Sweet corn fruit is one of the food favored by the people of Indonesia. The growth and yield of sweet corn can be increased by fertilizing. Research on the response of sweet corn growth to organic and NPK fertilizer was conducted in the Terong Tawah Village, West Lombok Regency. The purpose of this research was to determine: (1) response of the growth of sweet corn to the organic fertilizer treatment, (2) response of the growth of sweet corn to the NPK fertilizer treatment, (3) the effect of the interaction between organic and NPK fertilizer on the growth of sweet corn. The growth parameters of sweet corn are stem height, leaf lenght, number of leaf and stem diameter. Research data were analyzed using analysis of variance. The results showed that: (1) sweet corn growth has a positive response to the organic fertilizer, organic fertilizer can increas stem height, leaf lenght, number of leaf and stem diameter, (2)ÃÂ sweet corn growth has a positive response to the NPK fertilizer, NPK fertilizer can increase allÃÂ growth parameter, (3) the interaction between organic and NPK fertilizer has no significant effect on all growth parameters, (4) the optimum dose of organic fertilizer is 1.5 kg m-2 of agricultural land, (5) The treatment of 6 g NPK fertilizer was better than other treatments.